Análisis dinámico de la suspensión Pull Rod y Push Rod para el vehículo eléctrico tipo monoplaza - Villarreal Sarmiento, Carlos; Rodríguez Alcalá, Juan; Valverde Granja, Agustín (Vía innova, 2014)
SENA was proposed as a challenge to design and build an electric vehicle type formula for competitions nationwide. The subject matter of this article is to perform dynamic analysis Pull-Rod and Push-Pull the car suspension for optimum relationship between stability, weight and strength, seeking to improve performance race car. Another important aspect of the system is driver safety, a fault in this system may lead to loss of limb or life.